COMPARATIVE ANALYSIS OF BIOLOGICAL AND BIOCHEMICAL VENOM CHARACTERISTICS OF NORTH AND SOUTH AMERICAN Crotalus (SERPENTES: VIPERIDAE) SNAKE SPECIES: AN INTRODUCTORY APPROXIMATION TO UNDERSTAND THEIR BIOLOGICAL FUNCTIONS - SÁNCHEZ, ELDA E. (Saber (Cumana), 2016)
In this study, venom samples of rattlesnakes from the United States of America and Venezuela Bolivarian Republic were tested for their gelatinase, fibrinolytic, hemorrhagic and coagulant activities, as well as inhibition of platelet function. Electrophoretic titration curves on polyacrylamide gel were used to compare protein composition. There were different protease activities in the venoms. Hemorrhagic activity showed high geographic variation, but northern specimens had a higher trend in this parameter. Differences in venom protein conformation were palpable between snakes from the North and South America. There was a distinct protein composition among all venoms, several venoms presented hemorrhagic and fibrinolytic activities, and different performance on platelet assays. These results demonstrate the interesting differences between North and South America Crotalus venoms.